Controlling Differential Settlement of Highway Soft Soil Subgrade A New Method and Its Engineering Applications - Zhu, Hanhua; Wu, Zhijun; Chen, Mengchong; Zhao, Yongli (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book presents a new method for controlling the "bridge-head bumping" in soft soil ground based on years of practical on-site experience, which will be a valuable guide for engineers in Civil Engineering and Geotechnical Engineering. The soil properties of soft soil ground have the characteristics of big void ratio, high compressibility, high water content, low impermeability, low strength, strong structure and strong sensitivity. As a result, the soil ground presents very high rheological property. Therefore, controlling the "bridge-head bumping" in soft soil ground is essential for controlling the amount of the soil rheology induced unstable successive settlement. Based on the deformation compatibility and control theory of structure, this book proposes strategies to improve the design method of soft soil ground and the effective "bridge-head bumping" control method. .